A specific surgical operation for frenectomy in the upper lip of a young man in his forties: Case report - Issa Saad; Mohamad Salem Rkab; Ahmad Al Manadili; Marwan Al-Raeei; Chadi Azmeh; Ammar Nasser Agha; Waad Omran; Ahmad Suliman; Amer Badwi; Ahmad Daghstani; Wasim Alsobh; Ziad Khaita; et al. (Elsevier, 2023)
The process of removing a frenulum is one of the specialties of cosmetic dentistry. Inside the mouth there are two tissues known as the frenulum. This tissue includes both the teeth and the gums. It is usually divided into the frenulum of the tongue, which is the space between the level of the mouth and the tongue. Its function is to prevent the tongue from moving freely, which is why doctors recommend removing it. While the other section is known as lip frenulum, which is when the lip is too high, which forms an obstacle in front of the front teeth and pushes them away from each other. Also, this problem requires frenulectomy surgery. In this case report, we present a case of surgery performed to remove the upper labial frenulum in a patient in his forties. The previous patient visited the clinics of the International University for Science and Technology complaining of a massive diastema in his upper jaw. Therefore, we performed surgical resection of the superior labial frenum. We administered local anesthesia to the patient in order to perform the surgical procedure. We monitored the patient's condition for two and a half weeks in order to ensure his recovery and the success of the surgery.